Evaluation of Areca palm renewable options to replace disposable plastic containers using life cycle assessment methodology - Gautam, Anirudh (2021)
In spite of raising awareness of the environmental impacts associated to the production and utilization of plastics, in many situations, the use of plastics is advantageous, and options are still unavailable or under development, representing an opportunity to develop more sustainable options, such as less energy intensive solutions. In this work, the LCA methodology is used to evaluate the environmental impacts of boxes, bowls and plates produced using Areca palm (Areca catechu) sheath, a waste material common in southern India. The inventory is a combination of primary data from a company in India, complemented with secondary data from the Ecoinvent v2.1 (Simapro V7.3). Results show that the main contributors to the potential environmental impact categories and the most energy intensive life cycle steps, are transportation, shipping and electricity generation. Carbon footprints of 1180, 1033 and 1090 kg CO2eq/ton were obtained for Areca boxes, plates and bowls, respectively. Plates made from Areca palm sheath have lower environmental impacts than plastic plates, except in the ozone layer depletion and terrestrial toxicity impact categories.